Lithium-ion battery performance enhanced by the combination of Si thin flake anodes and binary ionic liquid systems. Issue 4 (24th June 2020) - Hosoya, Kei; Kamidaira, Toshiki; Tsuda, Tetsuya; Imanishi, Akihito; Haruta, Masakazu; Doi, Takayuki; Inaba, Minoru; Kuwabata, Susumu
Abstract : An appropriate combination of Si anodes and binary bis(fluorosulfonyl)amide-based ionic liquid electrolytes significantly improves Li-ion battery performances. Abstract : The use of ionic liquid (IL)-based electrolytes is one of the methods for solving various problems that pertain to large-capacity anodes, such as Si and Li, for next-generation lithium ion batteries (LIBs). There is insufficient information about the combination of such anodes and IL electrolytes. In the present study, a Si thin flake, which is one of the promising Si anode active materials, and binary IL electrolytes, 83.3–16.7 mol% 1-ethyl-3-methylimidazolium (bis((fluorosulfonyl)amide)) ([C2 mim][FSA])–lithium bis(trifluoromethanesulfonyl)amide (Li[TFSA]), 83.3–16.7 mol% [C2 mim][FSA]–lithium (bis((fluorosulfonyl)amide)) (Li[FSA]), and 50.0–50.0 mol% [C2 mim][FSA]–Li[FSA], were used for collecting various information on the battery performance, morphology variation of the Si thin flake, and chemical species in the solid electrolyte interface (SEI) layer. Operando scanning electron microscopy (SEM) and ex situ X-ray photoelectron spectroscopy (XPS) revealed that the SEI layer composition depends on the Li salt species and that their molar fractions in the binary IL electrolytes strongly affect the morphology variation in the Si thin flakes during the charge process. When the favorable Li conductive components, e.g., LiF and Li3 N, were abundantly contained in the SEI layer, the charge and discharge behavior of the Si thin flake anode was greatly improved. The best battery performance was obtained by the combination of the Si thin flake composite anode and the 50.0–50.0 mol% [C2 mim][FSA]–Li[FSA]. Discharge capacity above 1100 mA h g −1 was achieved even after 500 cycles under the charge and discharge conditions at a 3C rate.